Assessment of seismic spatiotemporal characteristics and migration distance in the Badong section of the Three Gorges Reservoir Area - Guoyong Duan; Fei Li; Kongwei Wang; Yaobo Xu (Earthquake Research Advances)
This paper aims to elucidate the seismic characteristics of the Three Gorges Reservoir area after impoundment and investigate the seismic source migration. Based on the seismic data analysis from the Badong segment in the Three Gorges Reservoir area, we assessed the local temporal and spatial variations in the frequent earthquakes. Correlation analysis was conducted to investigate the relationship between changes in reservoir water levels and the occurrence of reservoir-induced earthquakes. Additionally, we examined the regularity of earthquake occurrences at the exact location during different periods. Based on the fault mechanics principles, a formula was derived to estimate the length of open and wing-shaped rupture at the hypocenter under the influence of pore or excess pore water pressure. The results reveal that reservoir-induced seismicity demonstrates short-term cycles characterized by alternating ''active periods'' and ''quiet periods,'' as well as long-term cycles with the combined periods. The probability of earthquakes occurring within one year ​at the epicentre is relatively high and decreases after four years. The derived formula can be utilized to estimate the seismic migration distance at the epicentre in the short term. These research findings provide valuable insights for analyzing the regularity of reservoir-induced earthquake activities and understanding the mechanism of seismic source migration.